Mitigation of Amyloidosis with Nanomaterials - Ke, Pu Chun (Adv Mater, 2019)
Amyloidosis is a biophysical phenomenon of protein aggregation with biological and pathogenic implications. Among the various strategies developed to date, nanomaterials and multifunctional nanocomposites possessing certain structural and physicochemical traits are promising candidates for mitigating amyloidosis in vitro and in vivo. In this Research News, we introduce the mechanisms underpinning protein aggregation and toxicity, and highlight opportunities in materials science to drive this interdisciplinary field forward. Advancement of this emerging frontier hinges on exploitation of protein self-assembly and interactions of amyloid proteins with nanoparticles, intra- and extra-cellular proteins, chaperones, membranes, organelles and biometals.